Differential influences of serum vitamin C on blood pressure based on age and sex in normotensive individuals - Huang, Rui; Song, Linhua; Zhao, Jingbo; Lei, Yuhua; Li, Tian (Frontiers in Nutrition, 2022)
Aim Hypertension is among the most prevalent chronic diseases with diverse etiology, affecting over 1 billion people globally. In numerous studies, vitamin C inversely correlated with blood pressure and was suspected to have antihypertensive properties. Currently, there is conflicting evidence regarding the relationship between vitamin C and blood pressure, with most studies being conducted on hypertensive subjects. The principal objective of this project was to investigate the relationship between vitamin C and blood pressure in normotensive adult subjects. Methods A total of 2,533 individuals aged 20 years and above were enrolled in the present study from the National Health and Nutrition Examination Survey (NHANES) 2017-2018. Outcome variables were systolic blood pressure (SBP) and diastolic blood pressure (DBP). Serum vitamin C was regarded as an independent variable. EmpowerStats software and R (version 3.4.3) were used to examine the association between vitamin C and SBP or DBP. Results Vitamin C was reversely correlated with both SBP (β = −0.02, 95% CI: −0.03 to −0.00, p = 0.0306) and DBP (β = −0.02, 95% CI: −0.04 to −0.01, p = <0.0011) after adjusting all covariates. This reverse relationship may be affected by a number of factors, including a person’s gender, age, race, and ethnicity. A U-shaped association between vitamin C and SBP in females and an inverted one between vitamin C and DBP in males were detected, respectively. We further calculated the inflection points at 90.3 μmol/L for females and 40 μmol/L for males. It is somewhat surprising that a reverse U-shaped distribution between vitamin C and SBP and DBP in people over 50 was detected, and the point of inflection of vitamin C were all located at 40 μmol/L. Conclusion Vitamin C was negatively correlated with both SBP and DBP in this cross-sectional analysis. However, a U-shaped relationship and an inverted one were also observed in certain people, which implied that, though vitamin C is considered a vital antioxidant, maintaining vitamin C at appropriate levels may be beneficial according to different populations.